Discontinuation of Imatinib in a Child With Chronic Myeloid Leukemia. Issue 1 (January 2020) - Jeyaraman, Preethi; Naithani, Rahul
Abstract : Chronic myeloid leukemia (CML) has different disease biology with a more aggressive clinical course in children. Achieving treatment-free remission is the ideal goal for the pediatric CML population to avoid long-term toxicities of tyrosine kinase inhibitors. Here, we present our experience of stopping Imatinib in a pediatric patient of CML who had excessive weight gain with Imatinib. He is currently maintaining treatment-free remission for 15 months after stopping therapy at the time of last follow-up. The patient also had normalization of body mass index with the stopping of Imatinib.